Integrated Community Empowerment to Support Health, Education, and Sustainable Village Development in Tunong Krueng Kala - Ghrina Zikran; Muhammad Nasir; Ilhamsyah Siregar; Edy Miswar; Mahmuddin; Marwan Ramli; Mukhlis Yunus; Muhammad Adam; Mahdani; Said Musnadi; Iskandarsyah Madjid; Halimatusakdiah (Universitas Syiah Kuala, 2026)
Rural communities often face interrelated problems in health, education, environmental sanitation, and local economic capacity, which hinder sustainable village development. Tunong Krueng Kala Village in Aceh Besar reflects this condition, where limited access to preventive health services, low educational support for children, inadequate environmental awareness, and underutilized local potential remain key challenges. This community service article aims to describe the implementation and outcomes of a multidisciplinary empowerment program designed to strengthen community capacity through locally relevant interventions. The program was conducted through a participatory community service approach involving situation analysis, problem identification, program planning, implementation, and evaluation. The target community consisted of village residents from different age and occupational groups, while the implementing team involved university students from multiple disciplines under academic supervision and in collaboration with village authorities and local community members. The activities included blood pressure screening and hypertension education, basic literacy support for children, educational games and history learning activities, nutrition-oriented local food processing using moringa leaves, livestock health education, and environmental awareness campaigns through hygiene education and community clean-up actions. The results show that the program produced positive responses and practical benefits across several sectors. In the health activity, blood pressure screening of 24 adult participants found that only 50% were in the normal category, while the rest were classified as pre-hypertensive to moderate-severe hypertensive, indicating the importance of early detection and health education at the village level. Educational activities increased children’s enthusiasm and participation in learning, while local food processing and livestock health activities improved community knowledge and opened opportunities for household-level application. Environmental activities also strengthened awareness of hygiene and collective responsibility for village cleanliness. Overall, the program demonstrates that multidisciplinary, local potential-based community service can serve as an effective model for strengthening rural community capacity and supporting sustainable development at the village level.